Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3340/jkns.2012.51.3.127
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Prognostic Factors Relating to Postoperative Survival in Spinal Metastases

Abstract: ObjectiveTo analyze the prognostic factors thought to be related with survival time after a spinal metastasis operation.MethodsWe retrospectively analyzed 217 patients who underwent spinal metastasis operations in our hospital from 2001 to 2009. Hematological malignancies, such as multiple myeloma and lymphoma, were excluded. The factors thought to be related with postoperative survival time were gender, age (below 55, above 56), primary tumor growth rate (slow, moderate, rapid group), spinal location (cervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 35 publications
(79 reference statements)
4
29
0
2
Order By: Relevance
“…Yang et al (217 patients) analyzed the prognostic factors associated with survival time after a spinal metastasis operation and found that patients who underwent decompressive laminectomy without instrumentation had a median survival of 5.0 months, whereas those who underwent decompressive laminectomy with instrumentation had a median survival of 9.0 months, and the difference between the two was not significant. 36 These authors also analyzed anterior corpectomy and did not stratify survival, complications, functional status, or other factors by tumor type or operation.…”
mentioning
confidence: 99%
“…Yang et al (217 patients) analyzed the prognostic factors associated with survival time after a spinal metastasis operation and found that patients who underwent decompressive laminectomy without instrumentation had a median survival of 5.0 months, whereas those who underwent decompressive laminectomy with instrumentation had a median survival of 9.0 months, and the difference between the two was not significant. 36 These authors also analyzed anterior corpectomy and did not stratify survival, complications, functional status, or other factors by tumor type or operation.…”
mentioning
confidence: 99%
“…17 Patient-specific indications include life expectancy The stereotactic radiosurgery treatment plan. 17 Patient-specific indications include life expectancy The stereotactic radiosurgery treatment plan.…”
Section: Integration Of Radiosurgery With Spinal Surgerymentioning
confidence: 99%
“…17 There are typically three patient populations that would benefit from radiosurgery. This stands in contrast to conventional radiotherapy, in which typically 10 doses of 3 Gy each are given over the course of 2 weeks.…”
Section: Clinical Indications For Isolated Spinal Radiosurgerymentioning
confidence: 99%
“…Approximately 20 % of spinal metastasis cases exhibit neurological deficit due to spinal cord compression [4]. Untreated spinal metastasis results in the deterioration of life quality due to severe neurological deficits and intractable pain, which can shorten life expectancy with complications [5].…”
Section: Introductionmentioning
confidence: 99%